Radioactive metals in red mud - Kolobov, G.А.; Kirichenko, А.G.; Vodennikova, О.S.; Panova, V.О. (Вопросы атомной науки и техники, 2020)
The radioactivity of alumina production materials was analyzed. The main information on the content of radioactive metals in bauxite and red mud is presented. Technologies for the extraction of radioactive metals from red mud are considered.